The evolution of the genome (Elsevier Academic, 2005)
The Evolution of the Genome provides a much needed overview of genomic study through clear, detailed, expert-authored discussions of the key areas in genome biology. This includes the evolution of genome size, genomic parasites, gene and ancient genome duplications, polypoidy, comparative